2011
DOI: 10.1021/ma2002504
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Dynamics of Polybutadiene in Nanoscopic Confinement As Revealed by Field Cycling 1H NMR

Abstract: INTRODUCTIONApplying electronic (fast) field cycling (FC) NMR, Kimmich and co-workers have performed extensive studies on the collective dynamics in (bulk) polymer melts. 1 As a result, a generic dispersion behavior has been found for the dipolar fluctuations of polymer segments. The NMR relaxation dispersion exhibits characteristic power-law regimes and shows a crossover from a dispersion predicted by the Rouse model for short polymer chains to that of entangled polymer dynamics which can be described by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…However, higher mobility than predicted in the regime II was found, indicating a less static tube constraint [61]. Regime 0 and I are instead usually investigated with fast-field cycling experiment [62][63][64].…”
Section: Polymer Physicsmentioning
confidence: 99%
“…However, higher mobility than predicted in the regime II was found, indicating a less static tube constraint [61]. Regime 0 and I are instead usually investigated with fast-field cycling experiment [62][63][64].…”
Section: Polymer Physicsmentioning
confidence: 99%
“…In addition to structural aspects being of course among the most relevant molecular features, the presence of a variety of molecular motions dictate many of the properties of these systems, and directly affect their function. This includes, for instance, transport [1] and optical properties [2] of semiconducting polymers, mechanical behavior of constructing and rubbery polymers [3,4], activity of proteins [5], the stability of pharmaceuticals [6], ionic transport in glasses [7], and many others. Among the techniques used to probe molecular dynamics, NMR is known to be highly site-and frequency-selective, providing methods capable of studying molecular motion in a broad range of frequencies in chemical detail.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of "Template Synthesis", first introduced by C. R. Martin et al, was focused on the electrochemical or chemical template synthesis [116]. Later, the polymer template synthesis was widely studied and developed by many different groups, such as U Gosele's [60,117,118]; J. H. Wendorff's [119][120][121]; Steinhart's [118,[122][123][124][125][126][127][128][129][130]; T.…”
Section: Methods Of Preparation Of Polymer Nanostructures Using Aao T...mentioning
confidence: 99%
“…Likewise, Martín and coworkers [149] as well as Lagrené et al [203] did not detect any influence of confinement on molten PEO chains inside AAO templates. The entanglement network of molten high molecular weight polymers is likely to be more affected by the confinement than chain conformation [149,199,205]. Shin et al reported reduction of the viscosity of PS chains during capillary flow along AAO nanopores with dimensions smaller than that of the chain in bulk [199].…”
Section: Structure Of Amorphous Polymersmentioning
confidence: 99%